A multicenter, randomized, open label, two formulation, crossover bioequivalence trial of doxorubicin hydrochloride liposomal injection in Chinese patients with metastatic breast cancer - Jingshu Wang; Xiuping Lai; Herui Yao; Hui Yang; Xiaolong Cao; Xiaochen Wang; Ying Wang; Weiqi Nian; Xiaodong Zheng; Qingxiu Mai; Anding Liu; Xiaozhi Lv; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose The primary objectives of this trial were aimed at exploring the pharmacokinetic profiles and the human bioequivalence of an intravenous liposomal injection of doxorubicin hydrochloride in comparison with a reference formulation in Chinese patients diagnosed with metastatic breast cancer. Methods To achieve these goals, the trial employed a randomized, open-label, two-formulation crossover dosing strategy among Chinese patients with metastatic breast cancer. Pharmacokinetic (PK) evaluation was conducted through the collection of blood samples, and the liquid chromatography tandem mass spectrometry (LC/MS/MS) method was leveraged to quantify plasma concentrations of both liposome-encapsulated doxorubicin and non-encapsulated doxorubicin in patients. Throughout the trial, all adverse events observed in the patients were meticulously assessed. Results The results indicated that the maximum concentration (Cmax), AUC from time zero to the last measurable concentration (AUC0-t), and AUC extrapolated to infinity (AUC0-∞) of in vivo non-encapsulated doxorubicin after administration of both formulations fell within the 80.00%–125.00% range at a 90% confidence interval. Conclusion These findings strongly indicated that the tested formulations were bioequivalent to the reference formulation. The results also demonstrated that both formulations were well-tolerated, further establishing their safety profile in the context of metastatic breast cancer treatment. Trial registration Chinadrugtrials.org.cn Identifier: CTR20200878.